Association between better night‐shift nurse staffing and surgical outcomes: A retrospective cohort study using a nationwide inpatient database in Japan. Issue 2 (8th November 2022) - Morita, Kojiro; Matsui, Hiroki; Ono, Sachiko; Fushimi, Kiyohide; Yasunaga, Hideo
Abstract: Introduction: Although many studies have investigated the relationship between patient outcomes and the level of nurse staffing, little is known about the association between increased night‐shift nurse staffing and patient outcomes. In the Japanese universal health insurance system, a new scheme of additional financial incentives for acute care hospitals was launched in 2012 to increase the number of nurses during the night shift in general wards. The objective of this study was to investigate whether an additional financial incentive to increase night‐shift nurse staffing in general wards was associated with better patient outcomes. Design: Adoption of the above‐mentioned scheme of additional financial incentives was used as a natural experiment, and the difference‐in‐differences method was conducted to evaluate the effect of the scheme. The study was performed using a nationwide inpatient database and hospital information in Japan. Methods: To conduct a difference‐in‐differences analysis, first, hospitals with and without increased night‐shift nurse staffing were matched using propensity score matching. A patient‐level difference‐in‐differences analysis was then conducted. The intervention group comprised the hospitals that adopted the new scheme of additional financial incentives. The outcome measures were in‐hospital mortality, failure to rescue, and length of hospital stay. Results: Subjects were 403, 971 adult patients who underwent planned major surgeries in Japanese acute care hospitals from April 2012 to March 2018. The adjusted difference‐in‐differences estimates were not significant for in‐hospital mortality (odds ratio: 0.83; 95% confidence interval: 0.68 to 1.01; p  = 0.07) or failure to rescue (odds ratio: 0.92; 95% confidence interval: 0.73 to 1.14; p  = 0.44). The adjusted difference‐in‐differences estimate for length of hospital stay was significant (percent change: −3.2%; 95% confidence interval: −6.1 to −0.3%; p  = 0.029), indicating that the adoption of the scheme was associated with a decreased length of hospital stay. Conclusions: Increased night‐shift nurse staffing was not associated with a decrease in in‐hospital mortality or failure to rescue, but it was associated with a reduction in the length of hospital stay. It may be necessary to consider changes in policy content to make the policy more effective. The findings of this study are potentially useful for medical policymakers considering nurse staffing to decrease the length of stay, which may decrease costs. Clinical relevance: This study showed that increased night‐shift nurse staffing was not associated with a decrease in in‐hospital mortality or failure to rescue, but it was associated with a reduction in the length of hospital stay. The examination of the effectiveness of increasing nurse staffing during a specific shift in acute care hospitals is potentially useful for health policymakers worldwide in their considerations of future nurse staffing policies.